2007
DOI: 10.1021/es061276v
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Modeling of Emissions Trading of Highly Reactive Volatile Organic Compounds in Houston, Texas. 2. Incorporation of Chlorine Emissions

Abstract: As part of the State Implementation Plan for attaining the National Ambient Air Quality Standard for ozone, the Texas Commission of Environmental Quality has created a Highly Reactive Volatile Organic Compounds (HRVOC) Emissions Cap and Trade Program for industrial point sources in the Houston/Galveston/Brazoria area. This series of papers examines the potential air quality impacts of this new emission trading program through photochemical modeling of potential trading scenarios; this paper examines the air qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…This same study also found a maximum increase during morning hours, at the times of maximum rates of Cl 2 and HOCl photolysis, of 45 ppbv. [96,97] Because some of the peak enhancements of ozone concentrations predicted in these models are highly localised near chlorine radical precursor sources, the maximum predictions of the models are very sensitive to the grid cell dimensions used in the work. Wang et al [96,97] used a nested grid with horizontal spatial resolutions as small as 4 km.…”
Section: Condensed Chlorine Mechanism Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This same study also found a maximum increase during morning hours, at the times of maximum rates of Cl 2 and HOCl photolysis, of 45 ppbv. [96,97] Because some of the peak enhancements of ozone concentrations predicted in these models are highly localised near chlorine radical precursor sources, the maximum predictions of the models are very sensitive to the grid cell dimensions used in the work. Wang et al [96,97] used a nested grid with horizontal spatial resolutions as small as 4 km.…”
Section: Condensed Chlorine Mechanism Developmentmentioning
confidence: 99%
“…[96,97] Because some of the peak enhancements of ozone concentrations predicted in these models are highly localised near chlorine radical precursor sources, the maximum predictions of the models are very sensitive to the grid cell dimensions used in the work. Wang et al [96,97] used a nested grid with horizontal spatial resolutions as small as 4 km. In similar work, but with horizontal grid cell dimensions of 12-36 km, Sarwar and Bhave [98] modelled the effect of chlorine chemistry on ozone levels over the eastern half of the United States.…”
Section: Condensed Chlorine Mechanism Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Research over the past several decades has shown that the presence of reactive gas phase chlorine species, particularly chlorine radicals (Cl • ), can contribute significantly to atmospheric reactivity [1][2][3][4][5][6][7]. High concentrations of Cl • can lead to increased rates of Volatile Organic Compound (VOC) oxidation [8][9][10][11][12][13] and enhanced rates of O3 production in the troposphere [1,3,7,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These VOCs from solvent use result in heavy indoor air pollution (Celebi and Vardar, 2008;Dales et al, 2008;Kim et al, 2012), and especially, 18-40% of them are hazardous and harmful to human health (Wei et al, 2008(Wei et al, , 2009. Additionally, most VOC species emitted from solvent use are very chemically reactive, and hence play an important role in the formation of tropospheric ozone and fine particles (Derwent et al, 2007;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%